CURRENCY MANIPULATION FROM ISLAMIC MONETARY MANAGEMENT AND TRADE OUTLOOK - Widi, Fariza Rachman; Oetomo, Hening Widi (Online Journal of Islamic Management and Finance (OJIMF), 2022)
The word “competitiveness” in foreign exchange seems to dynamically widen. It does not solely refer to stronger against other currencies. Currency manipulation is the main reason, a monetary maneuver conducted by export-based countries to even depreciate their currency rate to maintain its competitiveness. Implemented years ago, it seems to become a warm topic once again since the US-China trade clash. The controversies emerged due to its tempting benefits to the exporter countries, yet hurting the importer countries. However, it seemingly violates no regulation in international trade law. Hence, the urge to review this policy from a wider perspective. This paper will review the currency manipulation from Islamic monetary management and trade principles, as Islam strongly urges in good pricing management which aims to benefit all trading parties and maqasidi resources control. The result shows that currency manipulation violates major aspects of Islamic monetary management and trade principles. The outcome also proposes the alternative principles scheme to elude the currency manipulation implementation for a long-term beneficial trade.